Different outcome measures and domains of functioning: 18 months follow-up of persons with dizziness. (June 2014) - Tamber, Anne-Lise; Bruusgaard, Kari A.; Bruusgaard, Dag
Abstract Aims: To explore changes in different outcome measures in a follow-up of persons with dizziness, and to investigate if these changes indicate different domains of functioning. Methodology: Sixty-eight persons with dizziness, mean age of 47 years, were included in an 18-month follow-up. Outcome measures used: the Vertigo Symptom Scale, Patient Specific Functional Scale, Disability Scale, Dizziness Handicap Inventory, and tests of Dynamic Visual Acuity, Single Leg Stance, and Walking Speeds. Major findings: We found significant improvements in impairments indicated by outcome measures of dizziness and visual acuity, and in activity and participation indicated by outcome measures of standing balance, patient-specific activities, disability and quality of life. Similar patterns of change were also found in subgroup analyses, except in gender. Correlations between change-scores were in the range r = 0–0.6. Significant correlations were found between change scores indicating body function and activity/participation (0.3 ≤ r ≥ 5). We found no correlations between self-report measures and tests. Conclusion: Comprehensive use of outcome measures addressing body function, activity and participation appear to provide information of changes in different domains of functioning. To enable broad and meaningful follow-up of patients with long-lasting dizziness, generic and condition-specific measures, self-reports and tests in different domains of functioning should be further explored.